2010
DOI: 10.1557/jmr.2010.0270
|View full text |Cite
|
Sign up to set email alerts
|

A plastic damage model for finite element analysis of cracking of silicon under indentation

Abstract: A modified plastic damage model that accounts for tensile damage and compressive plasticity as well as interactions among them is adopted to simulate the indentation-induced cracking of silicon under Berkovich, cube corner, and Vickers indenters. Simulations with this model capture not only the well-known cracking geometries in indented ceramics, such as radial, median, lateral, and half penny (Vickers indenter) cracks, but also the recent experimentally discovered quarter penny cracks under Berkovich and cube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
3
10
0
Order By: Relevance
“…The above results 13 and many other indentation tests [22][23][24][25][26][27][28][29] demonstrate that the subsurface residual deformation induced by indentation are phase transformations and defect. Zhang and Zarudi, 11 Zhang and Tanaka, 14,15 Biddut et al, 20,21 Lorenz et al, 38 Gassilloud et al, 39 and Wu et al 40,41 demonstrated that phase transformation always takes place before the emerge of dislocations and planar defects during nanoindentation and nanoscratching in silicon.…”
Section: Model Descriptionsupporting
confidence: 53%
See 2 more Smart Citations
“…The above results 13 and many other indentation tests [22][23][24][25][26][27][28][29] demonstrate that the subsurface residual deformation induced by indentation are phase transformations and defect. Zhang and Zarudi, 11 Zhang and Tanaka, 14,15 Biddut et al, 20,21 Lorenz et al, 38 Gassilloud et al, 39 and Wu et al 40,41 demonstrated that phase transformation always takes place before the emerge of dislocations and planar defects during nanoindentation and nanoscratching in silicon.…”
Section: Model Descriptionsupporting
confidence: 53%
“…20,21 At the same time, some authors reported experimentally the deformation-induced microdefects, such as stacking faults, dislocations and cracks in silicon under indentation with large loads and a large radius tip. 13,[22][23][24][25][26][27][28][29] For example, Zarudi and Zhang 13 analyzed the subsurface structure of indented mono-crystalline silicon by means of high-resolution a) electron microscopy on cross-section view samples. To understand the micro-structural changes with respect to indentation, a series of tests were conducted under total indentation loads of 30,40,50,70,90, and 100 mN, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The figure indicates that plasticity precedes cracking, in line with other results shown in Figure 1 that also show that cracking requires a higher load at smaller effective ball sizes. Wan, H.; Shen, Y.; Chen, Q. and Chen, Y. have elaborated on the plastic 'damage' preceding such cracking produced in silicon crystals with different type indenters [19]. Vodenitcharova, Borrero-López and Hofffman described the related cracking associated with scratching along different directions on {100} silicon crystal wafers [20].…”
Section: Indentation Fracture Mechanicsmentioning
confidence: 99%
“…This behaviour clearly predicts an increase in strength of silicon under loading conditions. In order to implement DP model to simulate deformation behaviour of silicon, the compressive crushing of concrete can be replaced by the compressive plasticity of silicon and tensile dilatancy of concrete be ignored [43].…”
Section: Determination Of Drucker-prager Parameters For Sph Modelmentioning
confidence: 99%